The Imbalance between Foxp3+Tregs and Th1/Th17/Th22 Cells in Patients with Newly Diagnosed Autoimmune Hepatitis. (27th June 2018) - Liang, Ma; Liwen, Zhang; Yun, Zhuang; Yanbo, Ding; Jianping, Chen
Abstract : This study is aimed at examining the potential role of regulatory T- (Treg-) Th1-Th17-Th22 cells in the pathogenic process of autoimmune hepatitis (AIH). The numbers of Foxp3 + Tregs and Th1, Th17, and Th22 cells were measured in 32 AIH patients using flow cytometry. Moreover, a murine model of experimental autoimmune hepatitis (EAH) was also established and used to investigate the function of Treg-Th1-Th17-Th22 cells in disease progression. AIH patients undergoing an active state had significantly decreased numbers of CD3 + CD4 + CD25 + Foxp3 + Tregs and increased numbers of CD3 + CD4 + CD25 − Foxp3 + T, CD3 + CD4 + IFN- γ + Th1, CD3 + CD4 + IL-17 + Th17, and CD3 + CD4 + IL-2 + Th22 cells as well as higher levels of Th1/Th17/Th22-type cytokines compared to AIH patients in remission and HC. Additionally, the numbers of CD3 + CD4 + CD25 + Foxp3 + Tregs were negatively correlated with the numbers of Th1-Th17-Th22 cells. Also, the serum levels of IL-17A and IL-22 were correlated positively with liver injury (ALT/AST), whereas the serum levels of IL-10 were correlated negatively with hypergammaglobulinaemia (IgG, IgM) in AIH patients. Interestingly, the percentages of spleen Tregs, expression of Foxp3 mRNA, and liver IL-10 levels decreased, whereas the percentages of spleen Th1-Th17-Th22 cells, expression of T-bet/AHR/ROR γ t mRNA, and liver IFN- γ, IL-17, and IL-22 levels increased in the murine model of EAH. Our findings demonstrated that an imbalance between Tregs and Th1-Th17-Th22 cells might contribute to the pathogenic process of AIH.